2004
DOI: 10.1186/1471-2393-4-20
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive evaluation of food fortification with folic acid for the primary prevention of neural tube defects

Abstract: BackgroundPericonceptional use of vitamin supplements containing folic acid reduces the risk of a neural tube defect (NTD). In November 1998, food fortification with folic acid was mandated in Canada, as a public health strategy to increase the folic acid intake of all women of childbearing age. We undertook a comprehensive population based study in Newfoundland to assess the benefits and possible adverse effects of this intervention.MethodsThis study was carried out in women aged 19–44 years and in seniors fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
99
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 32 publications
6
99
0
4
Order By: Relevance
“…27 Less than half of women surveyed in each State took periconceptional folate supplements. This finding is consistent with published studies based on Australian and overseas hospitalor service-based samples, 9,10,15,18,[28][29][30][31][32][33] and with US populationbased data. 11,12 Factors associated with not taking PFS, as in other populationbased studies, 11,12 are: being less than 25 years of age, having less education, being unmarried, having low family income, being born in non-English speaking countries, and unplanned pregnancy.…”
Section: Discussionsupporting
confidence: 82%
“…27 Less than half of women surveyed in each State took periconceptional folate supplements. This finding is consistent with published studies based on Australian and overseas hospitalor service-based samples, 9,10,15,18,[28][29][30][31][32][33] and with US populationbased data. 11,12 Factors associated with not taking PFS, as in other populationbased studies, 11,12 are: being less than 25 years of age, having less education, being unmarried, having low family income, being born in non-English speaking countries, and unplanned pregnancy.…”
Section: Discussionsupporting
confidence: 82%
“…15,21 Our results show that the inverse relation of plasma folate and the positive relation with homocysteine and adenoma recurrence were confined to nonusers of multivitamins in both studies.…”
Section: Discussionmentioning
confidence: 51%
“…Clearly, the optimal chemopreventive dose and timing of folate supplementation in humans has not been established. Although rates of NTDs have declined in the US and Canada following folic acid fortification of food products, 21,29 whether this mandate will also reduce rates of colorectal cancer is unknown. Furthermore, any long-term consequences of folic acid fortification are yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that such food fortification has resulted in a 20-70 % reduction in rates of pregnancies affected by NTD (3)(4)(5) .…”
mentioning
confidence: 99%